2019
DOI: 10.1111/resp.13617
|View full text |Cite
|
Sign up to set email alerts
|

Early life exposure to coal mine fire smoke emissions and altered lung function in young children

Abstract: Background and objective Long‐term respiratory risks following exposure to relatively short periods of poor air quality early in life are unknown. We aimed to evaluate the association between exposure to a 6‐week episode of air pollution from a coal mine fire in children aged <2 years, and their lung function 3 years after the fire. Methods We conducted a prospective cohort study. Individual exposure to 24‐h average and peak concentrations of particulate matter with an aerodynamic diameter <2.5 μm in diameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
36
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 44 publications
1
36
2
Order By: Relevance
“…Paediatricians need to continue to press home this point to politicians and urge strong action; Shao et al . 's study adds to the evidence that we are literally playing with fire if we do not do our utmost to protect little lungs from all outdoor (and indoor) pollutants.…”
mentioning
confidence: 92%
See 3 more Smart Citations
“…Paediatricians need to continue to press home this point to politicians and urge strong action; Shao et al . 's study adds to the evidence that we are literally playing with fire if we do not do our utmost to protect little lungs from all outdoor (and indoor) pollutants.…”
mentioning
confidence: 92%
“…In a recent publication in Respirology , Shao et al . followed up a cohort of children who were transiently exposed to high levels of atmospheric pollution as a result of serious fires . At 3‐year follow‐up, they demonstrated impairment of peripheral lung mechanics as measured by the forced oscillation technique (FOT).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These associations were not statistically significant for the 129 children exposed to the fire when 0–2 years old, perhaps because of the small sample size . Data on lung function for a subgroup of the ELF cohort (84 children) published elsewhere indicated that increasing mean daily PM 2.5 exposure was modestly associated with reduced respiratory system reactance (per 10 μg/m 3 increase: β‐coefficient, 0.26; 95% CI, 0.02–0.50) …”
mentioning
confidence: 99%